Assessment of Initial Stroke Severity by National Institute Health Stroke Scale (NIHSS) Score at Admission - Ghose, Swapon Kumar; Ahmed, Kazi Gias Uddin; Chowdhury, Ahmed Hossian; Hasan, ATM Hasibul; Saha, Kanol; Mahmud, Reaz; Joy, Nazmul Islam; Biswas, Rama; Sarkar, Md Sadekur Rahman; Rahman, Md Mahabubur; et al. (Journal of Dhaka Medical College, 2018)
Background: The National Institutes of Health Stroke Scale or NIH Stroke Scale (NIHSS) is a widely used tool for assessing stroke severity. We conducted this study to determine the severity of stroke patients admitted in a tertiary care hospital. Methods: This is a cross sectional study conducted in Department of Neurology, Dhaka Medical College Hospital from April 2016 to October 2016 involving 91 acute stroke patients. Result: About half (44%) of the patients were older than 60 years of age and mean age of the patients was 60.34(±16.1) years at onset and there is a slight female predominance (51.6%). Majority had hypertension (75.8%) followed by physical inactivity (67%), diabetes (37.4%), smoking (33%), obesity (23.1%), family H/O stroke (20.9%) and dyslipideamia (15.4%). Many patients were found to have hyperglycemia (14.3%) followed by hyperthermia (13.2%), hypotension (4.4%) and low oxygen saturation (3.3%) at the time of admission. Most of them had ischemic stroke (60%), followed by intracerebral hemorrhage (35%) and subarachnoid hemorrhage (5%). After leveling with NIHSS score more than half of the patients (51%) were found to be moderate grade on admission. Although, there was no association between risk factors of stroke and admission NIHSS score level, significant association was found between hypoxia and admission NIHSS score severity. Conclusion: Acute stroke patients, mostly have moderate grade of NIHSS score on admission. Hypertension, physical inactivity, diabetes, smoking, obesity, family H/O stroke and dyslipideamia are common risk factors observed among the patients which have no significant association with admission stroke severity determined by NIHSS score. There is significant association between hypoxia and admission NIHSS score severity. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 90-93